Ihsan Dalam Tinjauan Aksiologi Filsafat Islam - Tri Yugo; Surana, Dedih (UPT Publikasi Ilmiah, 2024)
As Islam's highest ethical value, Ihsan encompasses both spiritual and moral dimensions, involving perfection of action accompanied by sincere intentions and awareness of Allah's presence. Ihsan reflects values such as sincerity, justice, kindness, perfection, and responsibility, all of which are rooted in the belief that Allah is the supreme overseer of every human deed. This study uses a qualitative approach with a literature review method to explore the concept of ihsan from the axiographic perspective of Islamic philosophy. The analysis was carried out on hadith, classical literature on Islamic ethics, and contemporary works related to axiological philosophy. This research aims to identify moral and spiritual values in the concept of ihsan and its application in the daily life of Muslims. The results show that Ihsan plays an important role in various aspects of life such as business ethics, education, family relationships, and social interaction, and is relevant in modern contexts, especially in the era of globalization and technological development. Ihsan serves as a moral and spiritual foundation that helps Muslims maintain integrity amid social change, guiding them to live a meaningful life according to religious teachings